Electrochemical detection of ascorbic acid at MɡB₂- MWCNT and MɡB₂ /PEDOT hybrid modified glassy carbon electrodes - Banan, Darlene (2017)
Magnesium boride–multiwalled carbon nanotube (MgB2-MWCNT) modified electrode and poly-3,4-ethylenedioxythiophene/magnesium boride (PEDOT/MgB2) modified electrode were used to study the electrochemical oxidation of ascorbic acid (AA). Abrasive immobilization technique was used to modify the surface of glassy carbon electrode (GCE) with MgB2-MWCNT mixture through mechanical attachment method while electrodeposition technique was used to prepare PEDOT/MgB2 through electropolymerization process. The modified MgB2-MWCNT electrode showed good electrocatalytic properties towards AA oxidation. Compared to bare GCE, the MgB2-MWCNT modified electrode enhanced the oxidation current for AA by about two folds. At the MgB2-MWCNT modified electrode surface, the oxidation of AA occurred through diffusion-adsorption process, where a reduction of 60% of the activation energy required to diffuse AA at bare GCE was recorded when MgB2-MWCNT modified GCE was used. The MgB2-MWCNT modified electrode exhibits a lower detection limit and better sensitivity towards AA oxidation compared to bare GCE; limit of detection for AA is 1.2 μM and sensitivity is 89 mA/M AA. The MgB2-MWCNT modified electrode achieved good reproducibility for AA oxidation in which %RSD for both oxidation current and oxidation peak potential were in the range of 4-7% and 2-6% respectively. A recovery rate of 100.70 ± 4.01% was obtained when the MgB2-MWCNT modified electrode was used to detect AA in real samples. The PEDOT/MgB2 modified electrode demonstrated excellent electrocatalytic ability towards the mediation of AA oxidation. Cyclic voltammograms showed that the oxidation peak of AA was enhanced by about two folds and oxidation peak potential was shifted by about 100 mV towards the negative direction at the PEDOT/MgB2 modified electrode compared to bare GCE. Oxidation of AA at the PEDOT/MgB2 modified electrode surface was governed simultaneously by AA diffusion along with weak AA adsorption. The PEDOT/MgB2 modified electrode has a detection limit of 1.3 M and sensitivity of 82 mA/M AA where a reproducibility with %RSD of 5.65% for AA oxidation current and 4.20% for AA oxidation peak potential were obtained. Simultaneous detection of AA in the presence of dopamine (DA) at the PEDOT/MgB2 modified electrode indicates better selectivity over bare GCE, where a peak separation of about 300 mV was obtained between the oxidation peaks of AA and DA.